Economic Implications of China's Demographics in the 21st Century - Cheng, Kevin (IMF Working Papers; Working Paper ;, 2003)
This study assesses the economic implications of China's changing population in the 21st century using a numerical general equilibrium model. The simulations show that lower fertility rates yield lower saving rates. Since lower fertility rates reduce the future supply of labor, capital will become less productive. Consequently, if international capital mobility is high in China, a low fertility rate implies more future capital outflows. But if capital is less mobile, low fertility today lowers the domestic return to capital and raises the domestic return to labor. In addition, the paper finds no significant link between demographic structures and per capita income growth.